2019
DOI: 10.1051/0004-6361/201833849
|View full text |Cite
|
Sign up to set email alerts
|

Gaia-DR2 extended kinematical maps

Abstract: Context. The Gaia Collaboration has used Gaia-DR2 sources with six-dimensional (6D) phase space information to derive kinematical maps within 5 kpc of the Sun, which is a reachable range for stars with relative error in distance lower than 20%. Aims. Here we aim to extend the range of distances by a factor of two to three, thus adding the range of Galactocentric distances between 13 kpc and 20 kpc to the previous maps, with their corresponding error and root mean square values. Methods. We make use of the whol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…We recall that the basic assumptions of the Jeans equation are that the system is collisionless, axisymmetric, and in equilibrium. While the first condition represents a reasonable working hypothesis since collisional effects take place on much longer time scales than those that astrophysically relevant, the recent Gaia data have shown that the Milky Way is not in a stationary situation as there are large-scale gradients in all components of the velocity field and there are clear deviations from axisymmetry (Gaia Collaboration 2018b; Wang et al 2018;López-Corredoira & Sylos-Labini 2019;Wang et al 2020). The dynamical origin of such features represents an open problem that has been explored by several authors (Antoja et al 2018;Binney & Schönrich 2018).…”
Section: Corrections To the Jeans Equationmentioning
confidence: 99%
“…We recall that the basic assumptions of the Jeans equation are that the system is collisionless, axisymmetric, and in equilibrium. While the first condition represents a reasonable working hypothesis since collisional effects take place on much longer time scales than those that astrophysically relevant, the recent Gaia data have shown that the Milky Way is not in a stationary situation as there are large-scale gradients in all components of the velocity field and there are clear deviations from axisymmetry (Gaia Collaboration 2018b; Wang et al 2018;López-Corredoira & Sylos-Labini 2019;Wang et al 2020). The dynamical origin of such features represents an open problem that has been explored by several authors (Antoja et al 2018;Binney & Schönrich 2018).…”
Section: Corrections To the Jeans Equationmentioning
confidence: 99%
“…To determine the motion of the complexes with respect to the Galactic frame of reference, we transformed the heliocentric velocities to the LSR velocities by subtracting the motion of the Sun with respect to the LSR from the heliocentric velocities. In a number of studies (e.g., Trick et al 2019;López-Corredoira & Sylos Labini 2019) the velocity components of the motion of the Sun with respect to the LSR estimated by Schönrich et al ( 2010) of (U, V, W) = (11.1 +0.69 −0.75 , 12.24 +0.47 −0.47 , 7.25 +0.37 −0.36 ) km s −1 are used. However, recently, based on the Gaia DR2 data, the velocity components of the Sun's motion have been re-evaluated using, for example, stars (Li et al 2019;Ding et al 2019), open star clusters (Bobylev & Bajkova 2019), OB star samples (Bobylev & Bajkova 2018) and white dwarfs (Rowell & Kilic 2019).…”
Section: Motion Of L1147/1158 and L1172/1174 Complexesmentioning
confidence: 99%
“…Galactic modeling requires considering evolution and an asymmetric potential, as pointed out by Antoja et al (2018), who have revealed in our Galaxy many intriguing signals such as snail shells, arches and ridges, etc. The so called Galactoseismology (Widrow et al 2012(Widrow et al , 2014 concludes the non-equilibrium and non-stationary potential of the Milky Way, observed in many density or velocity asymmetries in Liu et al (2017); Wang et al (2018aWang et al ( ,b,c, 2019Wang et al ( , 2020a; Xu et al (2015); Gaia Collaboration: Katz et al (2018); Carrillo et al (2019); Trick et al (2019); López-Corredoira et al (2019a); López-Corredoira et al (2020) and reference therein, which are significant for us to understand the dynamical history of the Milky Way. There is no doubt we are entering into a golden era of the Galactoseismology by embracing Gaia (Gaia Collaboration et al 2018) parallax and proper motions.…”
Section: Introductionmentioning
confidence: 98%